2021
DOI: 10.3390/pr9040622
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Glass Fiber Reinforced Polypropylene Nanocomposites for Small Wind Turbine Blades

Abstract: This study aims to evaluate the effect of functionalized multi-walled carbon nanotubes (MWCNTs) on the performance of glass fiber (GF)-reinforced polypropylene (PP) for wind turbine blades. Support for theoretical blade movement of horizontal axis wind turbines (HAWTs), simulation, and analysis were performed with the Ansys computer package to gain insight into the durability of polypropylene-chopped E-glass for application in turbine blades under aerodynamic, gravitational, and centrifugal loads. Typically, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In this study, simulation and analysis are performed with the Ansys computer package to gain insight into the durability of polypropylene-chopped E-glass for application in turbine blades under aerodynamic, gravitational, and centrifugal loads. The authors found out that adding MWCNTs to glass fiber-reinforced PP composites had a substantial influence on deflection reduction, while that adding them to chopped-polypropylene E-glass had a significant effect on reducing the bias estimated by finite element analysis [9]. In another study, Unal Sen at al.…”
mentioning
confidence: 98%
“…In this study, simulation and analysis are performed with the Ansys computer package to gain insight into the durability of polypropylene-chopped E-glass for application in turbine blades under aerodynamic, gravitational, and centrifugal loads. The authors found out that adding MWCNTs to glass fiber-reinforced PP composites had a substantial influence on deflection reduction, while that adding them to chopped-polypropylene E-glass had a significant effect on reducing the bias estimated by finite element analysis [9]. In another study, Unal Sen at al.…”
mentioning
confidence: 98%